Digital Human Culture of Local Characteristic Cultural Resources: Expansion and Construction of Yangzhou Academic School - Ji, Chengxing (International Journal of Social Sciences and Public Administration, 2025)
As a significant regional academic school, the Yangzhou academic School holds considerable humanistic and historical value. With the widespread application of digital humanities technologies, the utilization and importance of data resource repositories have steadily increased. Serving as a distinctive local cultural resource, the Yangzhou University Library has established a Yangzhou academic School resource database. However, the database currently faces shortcomings such as delayed updates, outdated technology, limited content, and lack of classification. From the perspectives of digital humanities and the contemporary context of cultural development, this paper offers personal insights and recommendations on the significance of expanding the Yangzhou academic School data repository and approaches to its enhancement.